Determination of Plasminogen in Human Plasma by the Lysis Time Method - Berg, W; Korsan-Bengtsen, K; Ygge, J (Thrombosis and Haemostasis, 1966)
A one-stage lysis time system containing fibrinogen, streptokinase, thrombin, and a known, small amount of plasminogen was used to determine plasminogen in plasma.The known amount of plasminogen was added to the system in order to keep the lysis times relatively short when a highly diluted plasma was tested. High dilutions of plasma were used to reduce the influence of the plasma inhibitors.The calculation of the plasminogen concentration was made on the basis of the correlation: “plasminogen = fibrinogen/lysis time” which was valid in the system. The method allowed determination of plasminogen in plasma with varying fibrinogen concentrations, as the fibrinogen concentration in plasma was considered in the calculation.The presence of “spontaneous” plasmin activity in the plasma did not influence the plasminogen determination. Estimated by this method, the plasminogen content in plasma from 32 blood donors aged 25-45 years was 13.1 ±2.4 casein u/ml. The error of a single determination was 0.3 casein u/ml. The plasminogen content in plasma, determined with the present method, is about 3-4 times higher than the content found when a caseinolytic method is used.